2015
DOI: 10.1016/j.supflu.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-ideality on mixing of hydrocarbons and water at supercritical or near-critical conditions

Abstract: The mixing of a single-component or multi-component hydrocarbon (HC) droplet in supercritical or near-critical water (SCW/NCW) is modeled. Transport, thermodynamics, and phase equilibrium sub-models are used to estimate the relevant physical properties. We use a generalized Maxwell-Stefan (MS) expression to model the multi-component mass transfer and a diffusion driving force expressed in terms of fugacity gradients to account for effects of non-ideality on mass fluxes. We compare the ideal and non-ideal diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…In the plots of Figure 5, the mole fraction of the fuel (i.e., the heavy hydrocarbon) is given for the liquid and the gas phase as a function of chamber pressure (in terms of the reduced pressure of the fuel, p r = p/p c, f uel ) and temperature. The results prove that two-phase behavior can be predicted at pressures higher than the critical pressure of the injected fuel, similar to other works implementing the Redlich-Kwong, the Soave-Redlich-Kwong or the Peng-Robinson equations of state [9,11,14,[34][35][36][37]. As pressure is increased, the dissolution of the oxidizer (i.e., light gas) in the liquid phase is enhanced.…”
Section: Phase Equilibriumsupporting
confidence: 87%
See 1 more Smart Citation
“…In the plots of Figure 5, the mole fraction of the fuel (i.e., the heavy hydrocarbon) is given for the liquid and the gas phase as a function of chamber pressure (in terms of the reduced pressure of the fuel, p r = p/p c, f uel ) and temperature. The results prove that two-phase behavior can be predicted at pressures higher than the critical pressure of the injected fuel, similar to other works implementing the Redlich-Kwong, the Soave-Redlich-Kwong or the Peng-Robinson equations of state [9,11,14,[34][35][36][37]. As pressure is increased, the dissolution of the oxidizer (i.e., light gas) in the liquid phase is enhanced.…”
Section: Phase Equilibriumsupporting
confidence: 87%
“…It becomes important not to mix non-ideal and complex models with simpler ones, since better accuracy in these fluid states can be lost. For instance, He et al [11] show the effects of non-idealities on the diffusion process, where the so-called diffusion barrier can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Rigorously, the non ideal mixing of the species should be taken into account. Some authors [18][19][20][21] have shown that in the case of diffusionpredominant mixing close and above the critical point of the mixture, the effects of the non ideal mixing driving force is significant, especially at high temperature. In our case, we checked that the effects of the non ideal mixing driving force were negligible.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…t m = 0.0034 • ϵ −0.5 (18) The performance of other micromixers are collected in the literature [32,[34][35][36][37][38][39] and their mixing times are mostly higher than 1 ms. It should be reminded that all experiments previously published have been performed…”
Section: Micromixing Time and Mixing Performance Comparisonmentioning
confidence: 99%
“…∂y . Binary diffusion coefficients are obtained from high-pressure correlations and the thermodynamic factor, Γ, representing non-idealities in the diffusion process, is included in the diffusion driving force, d i [15,24,26]. The thermodynamic factor tends to 1 for an ideal mixture and it is identical to 1 for a pure substance.…”
Section: Transport Propertiesmentioning
confidence: 99%